Dobzhansky–Muller incompatibilities, dominance drive, and sex‐chromosome introgression at secondary contact zones: A simulation study. (19th June 2018) - Sciuchetti, Luca; Dufresnes, Christophe; Cavoto, Elisa; Brelsford, Alan; Perrin, Nicolas
Abstract: Dobzhansky–Muller (DM) incompatibilities involving sex chromosomes have been proposed to account for Haldane's rule (lowered fitness among hybrid offspring of the heterogametic sex) as well as Darwin's corollary (asymmetric fitness costs with respect to the direction of the cross). We performed simulation studies of a hybrid zone to investigate the effects of different types of DM incompatibilities on cline widths and positions of sex‐linked markers. From our simulations, X‐Y incompatibilities generate steep clines for both X‐linked and Y‐linked markers; random effects may produce strong noise in cline center positions when migration is high relative to fitness costs, but X‐ and Y‐centers always coincide strictly. X‐autosome and Y‐autosome incompatibilities also generate steep clines, but systematic shifts in cline centers occur when migration is high relative to selection, as a result of a dominance drive linked to Darwin's corollary. Interestingly, sex‐linked genes always show farther introgression than the associated autosomal genes. We discuss ways of disentangling the potentially confounding effects of sex biases in migration, we compare our results to those of a few documented contact zones, and we stress the need to study independent replicates of the same contact zone.